Questions on banking practice (London : The Institute of Bankers, 1965)
This tenth edition incorporates many changes resulting from legislation since the 9th edition in 1952, not least the Cheques Act, 1957. The current uniform customs and practice for documentary credit have also been incorporated as Appendix A. The index of 84 pages have been supplemented by an introductory classification of subjects and by appropriate subject headings for each page of the book. This volume should be no less valuable than its nine predecessors have undoubtedly been as a guide to accepted practice of bankers in England and Wales.
Revised and issued under the authority of the Council of the Institute of Bankers.
Includes index.
rpm 03/05/2018
Loans
Keywords: Banking; Banking Practice